Penentuan masa kadaluarsa sebagai upaya kontrol kualitas sambal di usaha mikro kecil menengah (UMKM) - afthoni, muhammad; Alfanaar, Rokiy; Yoedistira, Chresiani (Jurnal Pengabdian Masyarakat Charitas, 2023)
Sambal holds a significant place in Indonesian culinary heritage, reflecting the traditions of past generations. To address the issue of improper sambal storage leading to a shorter shelf life, a new approach in packaging has been introduced. The objective of this community service project is to establish the appropriate shelf life for sambal and provide storage recommendations. Through testing under different conditions, it was found that sambal can last for 4 days at room temperature, while the recommended storage temperature is between 2 and 8 degrees Celsius for a duration of 2 weeks.